(3GdbdGFO aj JUMjM GdYbGFOs - (3CMeO Hf jMji Hf GdeQJVj Hf eaVd Hf efUhQ GdMSfj, GdegOj dOjf Gddg,J (B840 (3g` s
(3ChdgG (B:s
(3Chdg cJGH GdJhMjO eSCdI (B: (3GJab GdeSdehf Ydi MOhK GdYGde GdOgQ Hd bOjf dfG de jNd ef GdGYQGV GdeMOKI s
(3BNQgG (B:s
(3bhdg Udi Gddg Ydjg hSde dG jMd dYjf JQi Gdgd jYU aJWQa MJi jZjQ Gddg Gh jfJbd Ke cJGH GdbdGFO s
(3Vef eLehY , JQJjHgG (B: 3s
(3HgG fXGe GdJYbjHIs
(3NRGFfjI HQSe Gdabjg GdaGVd YeGO GdOjf jMji Hf CMeO GdHQWis
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B269 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B2 - (3U (B206s
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
Keywords: (3eJaQbGJs